Agronomic parameters, quality indices, and sensory attributes of virgin olive oils from Hojiblanca and Picudo varieties from three successive crop years. Issue 12 (18th August 2014) - Jimenez, Brigida; Callejón, Raquel; Sánchez‐Ortiz, Araceli; Ortega, Eduardo; Lorenzo, Maria Luisa; Rivas, Ana
<x xml:space="preserve">Abstract</x> The aim of this study was to analyse how the stage of fruit ripening of two common Spanish olive cultivars Picudo and Hojiblanca affected the agronomic parameters of the olive as well as the analytical parameters and sensory properties of the corresponding oils during three successive crop years. Both varieties ripened according to similar profiles in each monitored crop year. The oil content increased during fruit ripening in all studied crop years. There was an inverse relationship between moisture and oil contents of the olives throughout ripening. The quality parameter that underwent further changes regarding fruit ripening and crop year was free acidity. In both varieties, oils obtained from olives harvested at an early ripening stage had higher positive sensory attributes. Olive fruity and green leaf attributes decreased throughout ripening. In contrast, the apple attribute was not perceived in oils obtained from unripe olives. Therefore, to ensure an adequate oil content as well as good physicochemical and sensorial qualities in virgin olive oil, the optimal harvesting period for Picudo and Hojiblanca olives coincides with a maturity index between 2.81 and 3.85 and between 2.72 and 4.28, respectively. Practical applications: The increase in demand for virgin olive oil is not only due to its health properties but also to its organoleptic properties, which ultimately determine consumer preferences and choice. In native cultivars, it is essential to assess the impact of the ripening stage on the agronomic parameters and the quality of the resulting virgin olive oil for optimal exploitation of the grove. A three‐crop‐year study in two representative Spanish cultivars was performed to characterise both the olive fruit parameters and oil sensory characteristics at ten different stages of maturity. This analysis was used to determine the optimal stage of ripeness at which olives should be harvested to produce good quality oils in terms of physicochemical and organoleptic features, which may better fulfil consumer expectations. <inline-graphic xlink:href="ark:/27927/pgh2qxdbbn0" content-type="ejlt201400043-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> This study analyses how the stage of fruit ripening of Picudo and Hojiblanca olive cultivars affected the agronomic parameters of the olive as well as the analytical parameters and sensory properties of the corresponding oils during three successive crop years. This analysis was used to determine the optimal stage of ripeness at which olives should be harvested to produce good quality, which may better fulfil consumer expectations.